Heme Oxygenase Activity Correlates with Serum Indices of Iron Homeostasis in Healthy Nonsmokers - Ghio, Andrew J. (Biomark Insights, 2016)
Heme oxygenase (HO) catalyzes the breakdown of heme to carbon monoxide, iron, and biliverdin. While the use of genetically altered animal models in investigation has established distinct associations between HO activity and systemic iron availability, studies have not yet confirmed such participation of HO in iron homeostasis of humans. Carbon monoxide produced through HO activity will bind to hemoglobin in circulating erythrocytes, and therefore, blood carboxyhemoglobin (COHb) can be used as an index of HO activity. Using the second National Health and Nutrition Examination Survey, we tested the postulate that HO activity correlates with serum indices of iron homeostasis in healthy nonsmokers. The investigation included 844 lifetime nonsmokers (586 females) 18 years of age and older in the study population. Significant correlations were demonstrated between COHb and several indices of iron homeostasis including serum levels of both ferritin and iron and percentage iron saturation of transferrin. There was no significant association between COHb and hemoglobin, the largest repository of heme in the human body, which functions as the substrate for HO. We conclude that HO activity contributes to human iron homeostasis with significant correlations between COHb and serum ferritin and iron levels and percentage iron saturation of transferrin.